Entitlements: Options for Reforming the Social Safety Net in the United States. Issue 1 (November 2019) - Moffitt, Robert A.; Ziliak, James P.
A combination of demographic aging and diversification, volatile business cycle conditions, stagnant real wages, declining employment, and policy choices have increased the need to examine the adequacy of the U.S. social safety net. Is it accomplishing what it is designed to do? Can it weather a fiscal storm? Current "entitlement" programs are in almost all cases providing important assistance to U.S. families and are improving families' well-being, but they face significant challenges that will require the attention of policy-makers around the country. Some programs may need a structural revamping, while others could do with incremental modifications. Because U.S. entitlement programs address complex social issues, they are themselves complex systems; it follows, then, that meaningful reform must be thoughtful and nuanced, eschewing political expediency. Further, federal support is needed for even more high-quality research that will provide evidence on the types of reforms that will achieve the goals of the programs.